PURCHASE DECISIONS ACEH CAKE UMKM - Tuwisna; Fandi Bachtiar; Sri Maisarah (CV. Radja Publika, 2026)
This study aims to test and analyze the influence of promotion through TikTok and product innovation on purchasing decisions in micro, small, and medium enterprises of Acehnese Traditional Cakes. The determination of the research sample uses the Purba formula. The sample used in this study was 96 consumers in micro, small, and medium enterprises of Acehnese Traditional Cakes who were willing to be respondents. The analytical method applied was multiple linear regression analysis. The results of the study indicate that promotion through TikTok partially has a positive and significant effect on purchasing decisions in micro, small, and medium enterprises of Acehnese Traditional Cakes in Banda Aceh city. Product innovation partially has a positive and significant effect on purchasing decisions in micro, small, and medium enterprises of Acehnese Traditional Cakes in Banda Aceh city. Promotion through TikTok and product innovation simultaneously have a positive and significant effect on purchasing decisions in micro, small, and medium enterprises of Acehnese Traditional Cakes in Banda Aceh city.